2019
DOI: 10.37358/rc.19.2.6984
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Bioimpedance Correlation with Quality of Life and Illness Perception in Hemodialysis Patients

Abstract: In hemodialysis patients malnutrition-inflammation syndrome, evaluated by biochemical laboratory analysis and through bioimpedance spectroscopy, was associated to impaired quality of life and with an increased risk of mortality. The present study goal was to investigate, in a cross-sectional analysis, performed in 122 hemodialysis patients, the association between biochemical parameters and bioimpedance-derived measurements the association of undernutrition with quality of life and illness perception. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…It was found that renal failure per se does not produce a gross defect in the capacity of patients from having a normal rate of albumin syntesis [16]. There are some studies that showed the lack of prompt success of nutritional intervention in correcting hypoalbuminemia, suggesting that nonnutritional factors may contribute to or be responsible for reduced albumin concentration in a fraction of hypoalbuminemic dialysis patients [17]. The morphological and functional integrity of the liver is vital to human health in general as well as to patients with renal disease.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that renal failure per se does not produce a gross defect in the capacity of patients from having a normal rate of albumin syntesis [16]. There are some studies that showed the lack of prompt success of nutritional intervention in correcting hypoalbuminemia, suggesting that nonnutritional factors may contribute to or be responsible for reduced albumin concentration in a fraction of hypoalbuminemic dialysis patients [17]. The morphological and functional integrity of the liver is vital to human health in general as well as to patients with renal disease.…”
Section: Resultsmentioning
confidence: 99%